2003
DOI: 10.1046/j.1365-2923.2003.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching sexual history taking to medical students and examining it: experience in one medical school and a national survey

Abstract: Both teaching and examining of sexual history taking skills are possible and are likely to occur increasingly in UK medical schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 15 publications
0
39
0
6
Order By: Relevance
“…Essa estratégia pedagógica permitiu aos docentes questionar opiniões e atitudes dos estudantes diante de temas sexuais com o acolhimento de eventuais desconfortos. Assim, essa prática propiciou o treinamento dos estudantes em conversar confortavelmente sobre sexualidade e, posteriormente, facilitar a aquisição de habilidades de comunicação para a assistência 26,29 . No entanto, o número elevado de estudantes nos módulos do curso Cinesex pode ter protegido aqueles mais tímidos da exposição pessoal durante o debate dos temas.…”
Section: Reflexão Pedagógica Sobre a Experiênciaunclassified
“…Essa estratégia pedagógica permitiu aos docentes questionar opiniões e atitudes dos estudantes diante de temas sexuais com o acolhimento de eventuais desconfortos. Assim, essa prática propiciou o treinamento dos estudantes em conversar confortavelmente sobre sexualidade e, posteriormente, facilitar a aquisição de habilidades de comunicação para a assistência 26,29 . No entanto, o número elevado de estudantes nos módulos do curso Cinesex pode ter protegido aqueles mais tímidos da exposição pessoal durante o debate dos temas.…”
Section: Reflexão Pedagógica Sobre a Experiênciaunclassified
“…TempleSmith et al (1999) reported on attitudes to sexual history taking in GP, with focus on working practises. A national survey by FitzGerald et al (2003) established that sexual history taking was undertaken in 17 UK Medical Schools, but assessed in six. In terms of using role play in this context, the literature remains sporadic.…”
Section: Practice Pointsmentioning
confidence: 99%
“…Several studies have shown that role play is a very effective method to enhance students' history-taking skills (see e.g., Schweickert, & Heeren, 1999;Skelton, & Matthews, 2001;Fitzgerald, Crowley, Greenhouse, Probert, & Horner, 2003;Wiskin, Roberts, & Roalfe, 2011). In China, Zhu et al also used this teaching method in fourth grade students, the results showed that students who accepted the teaching method had higher scores in history taking and medical record writing (see e.g., Zhu, Qiu, Qu, Xue, & Yan, 2014).…”
Section: Introductionmentioning
confidence: 99%